ANALISIS PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA BANJARMASIN - Umar Makawi; Normajatun Normajatun; Abdul Haliq (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
This study aimed to determine the picture is to know thecompetency influence to see with five indicators: motives, self concept, traits, skill, knowladge on performances employee of Dinas Perindustrian dan Perdagangan Kota Banjarmasin. The method used is a survey research approach and the data was collected using a questionnaire and that analyzed by using Multiple Linear Regression. The results of the descriptive analysisshowed that both competence and employee performance in very goodcategories. Statistical analysis showed competence affects the employee performance. This variable competence is to help increase the employee performance.